New Record to the Flora of Gujarat, India: Ceropegia vincaefolia Hook. (Family Asclapidaceae) - Maurya, Rupesh R.; Qureshimatva, Umerfaruq M.; Gamit, Sandip B.; Solanki, Hitesh A. (Indian Forester, 2018)
No Abstract.